Current perspectives of the Japanese Esophageal Oncology Group on the development of immunotherapy for esophageal cancer. (1st September 2022) - Kadono, Toru; Yamamoto, Shun; Kato, Ken
Abstract: Esophageal cancer is the seventh most common cancer worldwide and continues to have a poor prognosis. Starting with the development of immune checkpoint inhibitors for patients with metastatic melanoma, many clinical trials have been conducted to evaluate the efficacy and safety of immune checkpoint inhibitors against various malignancies. Although few effective drugs are available for patients with advanced esophageal cancer, two immune checkpoint inhibitors, nivolumab and pembrolizumab, have been approved as second-line treatments for advanced esophageal squamous cell carcinoma. Recently, immune checkpoint inhibitors have shown promising results as post-operative therapies and first-line treatments for advanced esophageal cancer. Nivolumab has been approved as a post-operative therapy based on the CheckMate-577 trial, and nivolumab, ipilimumab and pembrolizumab have been approved as first-line treatments based on the CheckMate-648 trial and the KEYNOTE-590 trial. In addition, many trials of immune checkpoint inhibitors plus pre-operative treatment or definitive chemoradiotherapy are ongoing. The Japan Esophageal Oncology Group was established in 1978 and has conducted numerous clinical trials, most of which have examined multimodality treatments. In the era of immunotherapy, Japan Esophageal Oncology Group is conducting a clinical trial studying multimodality treatment with an immune checkpoint inhibitor. JCOG1804E (FRONTiER) is a phase I trial to evaluate the safety and efficacy of nivolumab plus pre-operative chemotherapy followed by surgery. These results might improve the clinical outcomes of esophageal cancer patients. Abstract : Nivolumab and pembrolizumab have become the standard of care for the second-line treatment of advanced esophageal squamous cell carcinoma. Multiple clinical trials assessing immune checkpoint inhibitor-containing treatments for not only advanced cases but also for locally advanced cases are ongoing. One such example is the JCOG1804E trial.